Systemic Reform: Good Educational Practice with Positive Impacts and Unresolved Problems and Issues. - Anderson, Bernice Taylor; Brown, Costello L.; Lopez-Ferrao, Julio (Review of Policy Research)
This article describes the National Science Foundation's systemic reform programming, including major accomplishments and barriers to systemic reform. The challenges of systemic reform and new directions for education reform are discussed. The focus is on the results and challenges of policies implemented by the systemic initiatives, namely the mandate for the alignment of standards, curriculum, instruction, and assessment with the implementation of a standards-based K-12 mathematics and science education program; increased science and mathematics requirements for high school graduation; the delivery of intensive, high-quality professional development; and improvement in student achievement after three years of funding. A broader view of education reform in the future will require policymakers and educators to pay more attention to formulating mutually supportive policies across education, health, and social services; establishing fiscal policies that provide sufficient funding to ensure equitable outcomes; and revising accountability policies to facilitate rather than impede the reform efforts. Reprinted by permission of the publisher.